Child & adolescent : learners and learning principles - Guntalidad, Jose Antonio A.; Asuncion, Cythia S; Flores, Tobias; Beleño, Paz M.; Bejosano-Laforteza, Leah S.; Laforteza, Leobert C (Malabon City : Jimczyville Publications, 2019)
This book on the nature of adolescent learners and the fundamental principles of their learning is meant to provide our students in teacher education programs with an excellent background in preparation for professional teaching.
Unit 1. Biological dimensions of development -- Unit 2. Linguistic dimension of development -- Unit 3. Cognitive dimension of development -- Unit 4. Social Dimension of development -- Unit 5. Emotional dimension of development -- Unit 6. Learning Disabilities -- Unit 7. Physical Disabilities.
Includes bibliographical references.
Keywords: CHILD PSYCHOLOGY; CHILD DEVELOPMENT